2015
DOI: 10.1111/fwb.12651
|View full text |Cite
|
Sign up to set email alerts
|

Resident‐immigrant dichotomy matters for classifying wetland site groups and metacommunities

Abstract: Summary The fact that species have resident (autochthonous) or immigrant (allochthonous) status at any given locality may have strong implications for ecological analysis. We used wetlands and adult odonates as a model system to evaluate the resident‐immigrant dichotomy for two modes of community analysis: (1) grouping sites based on species compositional variation and (2) identifying metacommunity structure. We tested a hypothesis of gradient‐structured (non‐random) resident occurrence versus unstructured (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
28
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 10 publications
(33 citation statements)
references
References 71 publications
3
28
1
1
Order By: Relevance
“…This agrees with earlier findings of non-random resident versus random immigrant species occurrence within the meta-community context (Bried et al, 2015b) and helps to explain some structural patterns identified in that study. This agrees with earlier findings of non-random resident versus random immigrant species occurrence within the meta-community context (Bried et al, 2015b) and helps to explain some structural patterns identified in that study.…”
Section: Hypothesis Testingsupporting
confidence: 93%
See 4 more Smart Citations
“…This agrees with earlier findings of non-random resident versus random immigrant species occurrence within the meta-community context (Bried et al, 2015b) and helps to explain some structural patterns identified in that study. This agrees with earlier findings of non-random resident versus random immigrant species occurrence within the meta-community context (Bried et al, 2015b) and helps to explain some structural patterns identified in that study.…”
Section: Hypothesis Testingsupporting
confidence: 93%
“…A resident species occurrence designation, as determined previously using the same data set (see Bried et al, 2015a), required >20 individuals during at least one survey, tenerals on at least two surveys or species detection (teneral or not) on at least four surveys, with some exceptions (see Bried et al, 2015b). A resident species occurrence designation, as determined previously using the same data set (see Bried et al, 2015a), required >20 individuals during at least one survey, tenerals on at least two surveys or species detection (teneral or not) on at least four surveys, with some exceptions (see Bried et al, 2015b).…”
Section: Odonata Surveys and Resident Versus Immigrant Designationsmentioning
confidence: 99%
See 3 more Smart Citations